Development of active power filter using rectifier boost technique - Dygku Aniqnatasa Awg Osman; Rahimi Baharom; Dalina Johari; Muhamad Nabil Hidayat; Khairul Safuan Muhammad (Institute of Advanced Engineering and Science, 2019)
The development of active power filter (APF) using rectifier boost technique has been identified to compensate for the pulsating nature of the distorted supply current waveform of non-linear load. In this work, investigation is carried out on the operation of rectifier without any filters function. This is then extended to operate the rectifier converter with an active power filter function. APF function is implemented by enabling the closed-loop control using standard proportional integral control to rectify the distorted supply current to become continuous, sinusoidal and in-phase with the supply voltage waveform. Consequently, the total harmonic distortion (THD) level was reduced to meet the acceptable limit defined in the standard of IEEE-519 1992. The selected simulation results obtained from MATLAB/Simulink are presented to justify the proposed filter structure.